Pharmacological neuroenhancement and the ability to recover from stress - a representative cross-sectional survey among the German population - Christiana Bagusat; Angela Kunzler; Jennifer Schlecht; Andreas G. Franke; Andrea Chmitorz; Klaus Lieb (BMC, 2018)
Abstract Background Pharmacological neuroenhancement (PNE) refers to the use of psychoactive substances without doctor's prescription to enhance cognitive performance or to improve mood. Although some studies have reported that drugs for PNE are also being used to cope with stressful life situations, nothing is known about the relationship of PNE and resilience, i.e. the ability to recover from stress. This study aimed at investigating the relationship of PNE and resilience in the first representative population sample. Methods A cross-sectional survey in a representative sample of 1128 adults (age ≥ 18 yrs.) living in Germany was conducted. The use of PNE and related attitudes, perceptions and behaviours were assessed by structured interviews and self-report questionnaires. Stepwise logistic regression with backward elimination was conducted to identify potential risk factors for PNE use. Results Lifetime prevalence for the use of stimulating prescription drugs without medical indication was 4.3%, 10.2% for stimulating illicit drugs, 20.3% for mood modulating prescription drugs, and 23.4% for cannabis. Coping with stressful situations was more frequently reported as underlying motive for using stimulant or mood modulating prescription drugs than stimulating illicit drugs or cannabis. The individual perceived stress increased the risk of using stimulating prescription drugs (OR: 2.86; 95% Cl: 1.49-5.46) and the individual ability to recover from stress decreased the risk of using any substance for PNE and especially mood modulating prescription drugs (OR: .62; 95% Cl: .47-.81). Conclusions The non-medical use of prescription drugs for PNE appears to be more prevalent in subjects who are less resilient to stress. Tailored resilience interventions that improve the ability to adapt to and recover from stressors may prevent the use of prescription medication for PNE. Further research should disentangle the association between psychological resilience and PNE as well as examine the efficacy of resilience interventions in the prevention of PNE.